Preferential flow pathways in paddy rice soils as hot spots for nutrient cycling - Fuhrmann, Irabella; Maarastawi, Sarah; Neumann, Janice; Amelung, Wulf; Frindte, Katharina; Knief, Claudia; Lehndorff, Eva; Wassmann, Reiner; Siemens, Jan (Geoderma, 2019)
Crop rotations with maize and flooded rice lead to temporally aerobic soil conditions. This promotes the development of desiccation cracks in the soil, which can act as preferential flow pathways for water and solutes. We hypothesized that these cracks are enriched with organic carbon (C), plant nutrients and microbial residues (amino sugars) and that they can thus also serve as hot spots of fertilizer and C cycling. To test this hypothesis, we applied 13C-labelled rice straw and 15N-labelled urea to rice fields of the International Rice Research Institute (Los Baños, Philippines). We then traced the fate of the 13C-labelled rice straw and the 15N-labelled urea in crack and bulk soil and in microbial residues in two approaches, i) in the short term, i.e., 24 h after application of straw and fertilizer jointly with a dye tracer (Brilliant Blue) prior to maize seeding in the paddy - maize cropping system, as well as ii) in the long-term, i.e., during one year and for three different crop rotations (continuous paddy rice, paddy rice – maize, and paddy rice – maize with straw mulching and cover cropping). The short-term analyses of the dye tracer depth profiles showed that flow path areas decreased with increasing depth. A typical impermeable plough pan was not identified. Instead, we observed rapid infiltration of irrigation water down to 60 cm soil depth. The dyed flow paths were enriched in organic C (+12%) and plant nutrients (N: +21%, Ca2+: +59%, K+: +39%, Mg2+: +39%) relative to the bulk soil. The labelled straw and fertilizer quickly reached 60 cm depth with the dye tracer. We could not identify elevated microbial biomass along the flow paths, however, we did find larger microbial activities along the cracks in the long-term experiment than in the surrounding bulk soil. The increased activity fostered microbial uptake of fertilizer 15N along the cracks, which was detected mainly for fungal residues and only in the trials receiving straw (crack soil: 0.6 ± 0.1 mg glucosamine-15N kg soil−1, bulk soil: 0.2 ± 0.1 mg glucosamine-15N kg soil−1). We conclude that analysis of homogenized bulk soil samples can underestimate C and nutrient availability, as well as their microbial processing in paddy rice soils, when crack systems are not considered. •Straw application delays the appearance of desiccation cracks in paddy soils.•Flow paths in paddy rice soils are enriched with carbon and plant nutrients.•Intensified microbial activity increases fertilizer-N immobilization in soil cracks.